Development And Implementation of 5M Activity Based Digital Learning With a Cultural Approach - Husna, Nurul; Mariyam, Mariyam; Wahyuni, Rika; Utami, Citra; Prihatiningtyas, Nindy Citroresmi; Rosmaiyadi, Rosmaiyadi; Buyung, Buyung (STKIP Singkawang, 2024)
Today's educational transformation has led to digital-based learning. STKIP Singkawang is one of the universities implementing digital-based learning. The aim of this research is to determine the results of development, implementation, and student learning outcomes in implementing 5M activity-based digital learning with a cultural approach. The research method uses research and development (R&D) with a 4D development model without dissemination stages, namely the define, design, and develop stages. The research results show that the results of the development and implementation of digital modules for SBM courses can be presented more interactively, where all activities carried out in class are presented in writing in digital modules that contain 5M activities and are carried out synchronously and asynchronously. The majority of students' learning outcomes get very high scores, and student responses to learning are very positive.